2005
DOI: 10.1136/oem.2003.012609
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoconiosis after sericite inhalation

Abstract: Background: Between 1997 and 1999 three sericite plant workers in Paraná, Brazil, were diagnosed with pneumoconiosis. Aims: To investigate and describe the radiological, clinical, and pathological changes in miners and millers exposed to sericite dust with mineralogical characteristics of inhaled dust. Methods: The working premises were visited to examine the sericite processing and to classify the jobs according to make qualitative evaluation. Respirable dust was collected and the amount of crystalline silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, the development of pneumoconiosis due to exposure to mica or other phyllosilicates seems to require prolonged exposure to very high concentrations of dust, and the disease-relationship is often confounded by exposure to other occupational hazards, such as quartz and asbestos [ 6 , 37 ]. Nevertheless, several case reports indicate that high exposure to mica dust may cause pneumoconiosis distinct from silicosis in the absence of other occupational hazards [ 38 44 ]. While the number of experimental studies is scarce, toxicity from exposure to mica has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of pneumoconiosis due to exposure to mica or other phyllosilicates seems to require prolonged exposure to very high concentrations of dust, and the disease-relationship is often confounded by exposure to other occupational hazards, such as quartz and asbestos [ 6 , 37 ]. Nevertheless, several case reports indicate that high exposure to mica dust may cause pneumoconiosis distinct from silicosis in the absence of other occupational hazards [ 38 44 ]. While the number of experimental studies is scarce, toxicity from exposure to mica has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ACGIH (2001) identified the compromising nature of a publication with such co-exposures (i.e., Vestal et al, 1943), and Vestal et al was the only previously used publication that was not also referenced by ACGIH in 2021. Regrettably, however, ACGIH (2021) introduced newer studies that were compromised for the same reasons (Algranti et al, 2005; Landas and Schwartz, 1991; Raymond, 2014). Respective studies were used by ACGIH (2021) but dismissed from consideration in this review because they must not contribute to a risk assessment for respiratory exposure to mica only.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, spirometric lung function showed both obstructive and restrictive patterns, and diffusion capacity of carbon monoxide yielded both normal and attenuated patterns. Radiological investigations in some participants showed pleural thickening associated with calcification, 3,4 whereas in others groundglass opacity associated with bilateral micronodules and hyperdense lymph nodes were observed. Critical evaluation de lineated typical features, which were unlike other pneumo conioses.…”
mentioning
confidence: 94%
“…4,5 The use of advanced physicochemical analytical techniques, such as scanning electron microscopyenergy dispersive xray spectroscopy and analytical transmission electron microscopy of biopsy samples and bronchoalveolar lavage samples of patients with occupational exposure, confirmed the particles as pure mica. [3][4][5] One report 5 also showed an unusual autoimmune disease associated with mica pneumo coniosis.…”
mentioning
confidence: 98%
See 1 more Smart Citation